The role of adherence to the principles of the Basel Committee for Banking Supervision in the fight against bank fraud: applied research in the Central Bank of Iraq and the banks of rational and Rafidain (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Scientific and technological progress has been exploited in the financial and banking services sector ,The international information network has contributed to the promotion and facilitation of bank fraud, which has affected the country's economy, it’s national income, it’s financial and monetary policy, The distribution of incomes and consumption, and the negative impact on private business institution. And it’s financial and monetary institution , Including the Basel Committee for Banking Supervision and the supervisory authorities of the Group of Ten countries for this threat to the global economy, set a set of principles and procedures were laid down as rules to guide when evaluating the effectiveness of banking systems in banks. As technological progress contributes to the spread